AR-Game Pembelajaran Sumber Energi dan Pemanfaatannya Bagi Siswa Sekolah Dasar berbasis Android - Ibrahim, Millatu, Endah Sudarmilah, S.T., M.Eng (2015)
On education curriculum primary school there are still primary school curriculum 2013.2013 curriculum used the thematic. learningThe theme being a fastener some of its material subjects that must be conveyed teacher.The teaching and learning process at the present time membutuhan a new method to given the lectures to the students so that learning become lebik interactive.Based on that, researchers make application game learning with augmented reality.In developing this game of learning through several phases among others designing games with the data flow diagrams, collect data, and testing applications.In the game of learning are to be found quiz, matter, and the 3d designs as of objects in a quiz and material. The application of augmented reality game learning the source and energy benefits raised from a lesson always frugality energy to class 4. The application of this edugame tested in SDIT muhammadiyah al-kautsar gumpang kartasura on class IV A. Based on the data from the results of testing , we can conclude that the application will be used to help students in learn in interesting and interactive.